Multimorbidity and the combination of chronic non-communicable diseases and their relationship to all-cause mortality among Costa Rican older adults - Beatriz Novak (Población y Salud en Mesoamérica)
Objective: To estimate the prevalence of multimorbidity due to chronic non-communicable diseases, the prevalence of pairs and triads of these diseases and the respective associated mortality risks in older adults in Costa Rica. Methods: The data used belong to the study Costa Rica: Longevity and Healthy Aging Study. Gompertz models (adjusted for sociodemographic factors, health-related behaviors, and functional status) were estimated to assess the association of multimorbidity with all-cause mortality between 2005 and 2009. The study population comprised 2,565 individuals who provided data on all covariates at baseline. Results: The prevalence of multimorbidity was 42.6%. The five most frequent disease pairs combine hypertension with diabetes, coronary heart disease, respiratory conditions, arthritis, and osteoporosis (around 14%, 10%, 9%, 7%, and 6%, respectively). The most frequent disease triads were diabetes-hypertension-respiratory conditions and diabetes-hypertension-coronary heart disease (about 3% in both cases). Multimorbidity was associated with 64% increased mortality risk, not adjusting for functional limitations, and 37% when adjusting for functional limitations.  The following disease pairs at baseline increased the mortality risk, compared to persons without these combinations at baseline: diabetes-hypertension (49%); cancer-respiratory disease, diabetes-coronary heart disease, and diabetes-stroke (around two times); and cancer-hypertension and cancer-diabetes (around three times). The mortality risk among those with diabetes-hypertension-coronary heart disease and diabetes-hypertension-osteoporosis was twice that of persons without these diseases at baseline. Conclusion: There is a need to develop strategies to address the burdens that multimorbidity, particularly cardiometabolic multimorbidity, impose on individuals as well as on the healthcare system.